An Assessment of Multi-dimensional Factors Influencing Patronage of E-Commerce Channels in Beijing, China: Inputs for Loyalty Program - Liu, Fang (JPAIR Multidisciplinary Research, 2025)
Cognizant of the growing Chinese e-commerce as one of the fundamental elements of the modern world because of technological advancements, this empirical study investigated e-businesses that utilize a variety of digital channels, such as social media, websites, and specialized applications, to market their products. Through a quantitative-descriptive research method, this study assessed the factors influencing e-commerce patronage, including product type, product quality, pricing competitiveness, user experience, and information security. The respondents were 300 customers of Tiktok, TaoBao, and JingDong in Beijing, China, chosen through quota sampling, who completed a survey questionnaire as the primary instrument for gathering data to answer research problems and test the hypothesis. The results revealed that user experience is highly influential in e-commerce patronage. The impact of these elements on patronage may vary depending on user preferences, platform design, and the overall shopping journey. The availability of a wide range of products on e-commerce platforms attracts customers looking for diverse options, influencing their patronage decisions. Competitive pricing strategies, including discounts, promotions, and price comparisons, significantly influence customers' choice of e-commerce channels. Trustworthiness and security of payment methods, data protection, and overall transaction security play a crucial role in attracting and retaining customers. The factors influencing e-commerce patronage are not significantly affected by demographic characteristics such as age, sex, educational attainment, and income.
Keywords: Business and Management; assessment; factors, patronage; e-commerce; channel; quantitative-descriptive; China